TEACHING ENGLISH TO YOUNG LEARNERS AND THE FEATURES OF ELT TO ADOLESCENTS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study investigates the distinctive characteristics and methodological approaches in teaching English to young learners and adolescents, examining both theoretical frameworks and practical implications for classroom instruction. The research analyzes how age-specific developmental factors influence language acquisition processes and teaching strategies, with particular focus on the integration of cognitive development theory, second language acquisition principles, and age-appropriate pedagogical practices.